A medium-C martensite steel with 2.6 GPa tensile strength and large ductility. (15th April 2023) - Junkui, Li; Zhinan, Yang; Hua, Ma; Chen, Chen; Fucheng, Zhang
Abstract: Nanoscale lath martensite with high density dislocations and fine V carbides embedded in heterogeneous lamellar structure was produced in Medium-C (0.46%) martensitic steel through multistage rolling process followed by subsequent oil quenching and low-temperature tempering. Tensile properties show the yield strength, ultimate tensile strength and uniform elongation are up to 1809 MPa, 2590 MPa and 12.6%, respectively. The excellent combination of strength and ductility is comparable and even superior to other high-strength high-ductility metallic materials. In addition, the underlying mechanisms were briefly discussed. Graphical abstract: Image, graphical abstract